2020
DOI: 10.1177/1087054720964561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the SNAP25 on Integration Ability of Brain Functions in Children With ADHD

Abstract: Objective: The present study aimed to examine the effects of SNAP25 on the integration ability of intrinsic brain functions in children with ADHD, and whether the integration ability was associated with working memory (WM). Methods: A sliding time window method was used to calculate the spatial and temporal concordance among five rs-fMRI regional indices in 55 children with ADHD and 20 healthy controls. Results: The SNAP25 exhibited significant interaction effects with ADHD diagnosis on the voxel-wise concorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Recent fMRI genetic studies have analyzed the effects of rs3746544 in Chinese Han children with ADHD. For example, resting-state fMRI studies showed that the regional homogeneity of the default mode network and working memory index were higher in the TT group than in the TG group (Fang et al, 2019 ), and G allele carriers had higher voxel-wise concordance in the right anterior central gyrus, superior frontal gyrus, posterior central gyrus, and middle frontal gyrus than those with TT homozygotes (Yang et al, 2020 ). In our study, fNIRS revealed that in the go/no-go task, [Δavg oxy-Hb] in the DLPFC in the T/T group were significantly increased post- MPH 4w treatment, whereas no significant changes in [Δavg oxy-Hb] were observed after treatment in the G allele group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent fMRI genetic studies have analyzed the effects of rs3746544 in Chinese Han children with ADHD. For example, resting-state fMRI studies showed that the regional homogeneity of the default mode network and working memory index were higher in the TT group than in the TG group (Fang et al, 2019 ), and G allele carriers had higher voxel-wise concordance in the right anterior central gyrus, superior frontal gyrus, posterior central gyrus, and middle frontal gyrus than those with TT homozygotes (Yang et al, 2020 ). In our study, fNIRS revealed that in the go/no-go task, [Δavg oxy-Hb] in the DLPFC in the T/T group were significantly increased post- MPH 4w treatment, whereas no significant changes in [Δavg oxy-Hb] were observed after treatment in the G allele group.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR)-restriction fragment length polymorphism assays were used to determine SNAP-25 gene (GenBank Accession Number D21267) Mnl I (rs3746544) polymorphisms. The oligonucleotide primers used to determine the Mnl I polymorphisms within the SNAP-25 gene have been described previously (Yang et al, 2020 ). The primers used to amplify the SNAP-25 gene (Yang et al, 2020 ) were as follows: forward, 5-TTCTCCTCCAAATGCTGTCG-3 and reverse, 5-CCACCGAGGAGAGAAAATG-3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, previous studies have demonstrated that the step size does not dramatically affect the variance of dynamic properties of R-fMRI ( Liao et al, 2019 ). Therefore, we used a window length of 32 TR (64 s) and a step size of 4 TR (8 s) ( Yang et al, 2020 ). More importantly, different window length (48 TR/64 TR) were used to validate our results (see Supplementary Materials ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the step size does not significantly affect the variability of fMRI dynamic characteristics, but the empirical value is equal to one-tenth of the window length ( Liao et al, 2019 ). The window length and step size we used were based on previous literature ( Lou et al, 2021 ; Yang et al, 2022 ). The following dynamic measurements were calculated in each window:…”
Section: Methodsmentioning
confidence: 99%